Local Clonal Diversification and Dissemination of B Lymphocytes in the Human Bronchial Mucosa - Ohm-Laursen, Line; Meng, Hailong; Chen, Jessica; Zhou, Julian Q.; Corrigan, Chris J.; Gould, Hannah J.; Kleinstein, Steven H. (Frontiers in Immunology, 2018)
The efficacy of the adaptive humoral immune response likely requires diverse, yet focused regional B cell antibody production throughout the body. Here we address, in the first study of its kind, the B cell repertoire in the bronchial mucosa, an important barrier to antigens inhaled from the atmosphere. To accomplish this we have applied high-throughput Adaptive Immune Receptor Repertoire Sequencing (AIRR-Seq) to 10 bronchial biopsies from altogether four different sites in the right lungs from an asthmatic patient and a healthy control subject. While the majority of identified B cell clones were restricted to a single site, many were disseminated in multiple sites. Members of a clone were shared more between adjacent biopsies than between distal biopsies, suggesting local mucosal migration and/or a homing mechanism for B cells through the blood or lymph. A smaller fraction of clones spanned the bronchial mucosa and peripheral blood, suggesting ongoing trafficking between these compartments. The bronchial mucosal B cell repertoire in the asthmatic patient was geographically more variable but less diverse compared to that of the control subject, suggesting an ongoing, antigen-driven humoral immune response. We observed a subset of highly mutated and antigen-selected IgD-only cells in the bronchial mucosa. These cells were found at a high proportion in the asthmatic individual but also, albeit in lower proportion, in the healthy control subject.